2012
DOI: 10.1111/j.1399-0039.2012.01915.x
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of association between functional polymorphisms located within IL6R and IL6ST genes and systemic sclerosis

Abstract: Systemic sclerosis (SSc) is a complex autoimmune disease which genetic component has not been yet completely understood. IL6 encodes a cytokine with a crucial role in the development of autoimmunity and fibrosis and its actions mainly are controlled by IL-6 receptor (IL-6R). We aimed to investigate whether the functional genetic variants rs8192284 and rs2228044 previously associated with several autoimmune diseases, located within the IL-6 receptor (IL-6R) subunits IL6R and IL6ST genes, respectively, are invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…The frequency of the minor C allele of IL-6R Asp358Ala (rs2228145) found in this study for the control (34.7%, 95% IC 27 -43) was similar to Americans (39.6%) (Qi, Rifai and Hu, 2007), Spanish (39.3%) (Cenit et al, 2012), Polish (33.2%) (Kapelski et al, 2015) and lower than in Korean (44.5%) (Kim et al, 2004) populations. We have not found information about this polymorphism in T1D.…”
Section: Discussionsupporting
confidence: 61%
“…The frequency of the minor C allele of IL-6R Asp358Ala (rs2228145) found in this study for the control (34.7%, 95% IC 27 -43) was similar to Americans (39.6%) (Qi, Rifai and Hu, 2007), Spanish (39.3%) (Cenit et al, 2012), Polish (33.2%) (Kapelski et al, 2015) and lower than in Korean (44.5%) (Kim et al, 2004) populations. We have not found information about this polymorphism in T1D.…”
Section: Discussionsupporting
confidence: 61%
“…35,42,43 Also, no significant correlations were detected between this SNP and susceptibility to systemic sclerosis. 48 However, some studies reported an association of the IL-6R Asp358Ala allele C with increased risk of atopic dermatitis and decreased risk of RA. 46,49 It should be noted that the relatively limited sample size constitutes a major limitation of the present study that could result in a statistical power insufficient to detect small or moderate effects.…”
Section: Discussionmentioning
confidence: 99%
“…Response to biological therapy in RA Lack of association [35,[42][43][44] Risk of cardiovascular disease in RA Lack of association [29,45] RA susceptibility C allele associated with decreased risk [46] Disease activity in RA C allele in patients correlated with lower disease activity [47] Susceptibility to systemic sclerosis Lack of association [48] Susceptibility to atopic dermatitis Allele C correlated with increased risk of disease [49] Pharmacogenomics and Personalized Medicine 2021:14 years. Fifty-four patients had type 1 psoriasis, the rest had type 2 psoriasis.…”
Section: Il-6r Asp358alamentioning
confidence: 99%